Exploring the dietary changes and support required for healthy eating with female students at UK universities: Findings from focus group discussions - Eve F. A. Kelly; Merve Guney-Coskun; Michelle Weech; Rosalind Fallaize; Faustina Hwang; Julie A. Lovegrove (PLoS ONE, 2025)
Students’ diets often change when leaving home and starting university due to increased responsibility for their diet and finances. However, there is limited qualitative research with students at UK universities about how their diets change during the transition to, and whilst at university and the reasons for these changes. The aim of this study was to qualitatively explore three topics: 1) specific dietary changes reported by students at UK universities, 2) reasons for these dietary changes and 3) how students can be supported to eat more healthily. Fifteen students (100% female, 54% white) across different academic years (60% undergraduate and 40% postgraduate) from the Universities of Reading and Hertfordshire were recruited. Four online focus groups were conducted, ranging from groups of 2 to 6 participants, using a semi-structured topic guide. Discussions were recorded and professionally transcribed. Transcripts were coded and themes derived for each research topic using qualitative analysis software. After joining university, dietary changes commonly reported by the students included either increased or decreased fruit and vegetable intake, increased snacking behaviour, and increased alcohol and convenience food consumption. Common reasons for changes included limited budget, time management struggles, a lack of cooking skills, and peer influence. Students suggested that reduced cost of healthy foods on campus and cooking classes to learn new skills could help them to adopt a healthier diet. These suggestions could be used to guide future healthy eating interventions for university students.